Kelelahan Digital Di Era Media Sosial: Studi Tentang Kelebihan Informasi, Kecemasan, Dan Fear Of Missing Out (FOMO) - Wijaya, Faustin Venus; Gobai, Febbi Afrelia; Suciawan, Ariell Goldina; Biondy, Mel; Ardyan, Elia (STIM-LPI Makassar, 2025)
This study aims to examine the effect of information overload and anxiety on fear of missing out (FOMO) and social media fatigue. The study was conducted on 100 respondents who had experienced FOMO and social media fatigue, using a quantitative approach. Data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method through WarpPLS version 8 software. The results showed that information overload had a positive and significant effect on FOMO and social media fatigue, while anxiety had a positive and significant effect on FOMO, but was not significant on social media fatigue. In addition, FOMO was shown to have a positive and significant effect on social media fatigue. These findings provide theoretical contributions by strengthening the literature on the role of FOMO as a mediator in the relationship between information overload and social media fatigue, and underlining the complexity of the influence of anxiety on the social media user experience. Practically, these results are relevant for social media platform managers to develop strategies that reduce the negative impacts of FOMO and social media fatigue, such as healthier platform design and user education on time management on social media. This study has limitations in the limited sample size and cross-sectional design, so further research with a more diverse population and longitudinal approach is recommended to strengthen generalization and analysis of causal relationships.